Fungsi Garis pada Desain dan Sketsa - Lintang Widyokusumo (Bina Nusantara University, 2013)
In the early stages of designing a design, sketch is an initial beginning of the creation of a powerful idea. Preliminary sketch forms structured or free lines to try to catch an idea or a model that will be realized in the design or picture. The process behind the stunning design starts from a dot and lines to the structure and expanded into a variety of alternative designs. The role of a line is often underestimated and exacerbated by the increasingly rapid development of technology, which makes people lazy to explore manually. The strength of line/scratch built through a continuous training process produces bold, spontaneous, and characterized lines.